Assessment of fungal and thermo-alkaline post-treatments of solid digestate in a recirculation scheme to increase flexibility in feedstocks supply management of biogas plants. (April 2020) - Brémond, Ulysse; Bertrandias, Aude; Loisel, Denis; Jimenez, Julie; Steyer, Jean-Philippe; Bernet, Nicolas; Carrere, Hélène
Abstract: Agricultural biogas plants can suffer occasional feedstock shortages (poor harvest, storage …) and recirculation of solid digestate (SD) into digester has been identified as a simple way to offset methane production loss from these situations. Calculations show that recirculation of SD could offset for losses in plant methane production by up to 2.4%. In that context, two post-treatments were evaluated to enhance residual potential methane of agricultural SD. Effect of fungal solid state fermentation (SSF) of SD on subsequent methane production has never been explored before. It was hypothesized that: (i) ligninolytic fungi would be able to specifically use the complex fraction of SD for their growth and (ii) energy generation from the subsequent anaerobic digestion of the colonized SD will be enhanced. However, experiments showed that thermo-alkaline treatment of SD (used as alkalinization and sterilization process) and a high spawn level (20% w/w) were necessary to perform fungal SSF. Besides, the observed fungal activities on SD did not target specifically the most complex fractions. This led to uncontrolled organic matter losses and subsequent decreases of biodegradability and methane yield of SD (up to 50%). Therefore, fungal SSF of SD before its recirculation into biogas plants appeared not to be a viable option. Only thermo-alkaline treatment (CaO 2% w/w and 121 °C 30 min) enhanced methane yield of SD by 13% and decreased its complex fraction by 25%. Further studies on optimization of this post-treatment may enhance efficiency of SD recirculation strategy to offset plant methane production losses. Graphical abstract: Image 1038572 Highlights: SD recirculation could compensate loss in plant methane yield by up to 2.4%. Necessary sterilization and high spawn level to allow fungal SSF of SD. Observation of losses in biodegradability and methane yield of SD after fungal SSF. No specific degradation of the lignin-like fraction of SD during fungal SSF. Thermo-alkaline treatment increases residual methane potential of SD (+13%).